Editorial – Communication and internet policy: a critical rights-based history and future - Aphra Kerr; Francesca Musiani; Julia Pohle (Internet Policy Review, 2019)
This special issue of Internet Policy Review brings together a hand-picked selection of articles presented in the Communication Policy and Technology (CPT) section at the annual conference of the International Association for Media and Communication Research (IAMCR) in Eugene, Oregon (USA), 2018. With different theoretical perspectives, methodologies, and geographical scope, the five papers in this issue address how ideal-type rights and values are translated into highly variable rules, regulations, policies and practices in different countries and regions around the world. Drawing from their respective case studies, the papers examine a number of consequences of this gap for internet users, as citizens and consumers. Building on these papers, the editorial discusses some recent evolutions of the internet policy field, and introduces the critical and `engaged scholarship' approach that IAMCR and its CPT section have displayed over the years in their analyses of communication and internet policy.
Keywords: 330; IAMCR; user rights; state policy; communication rights; UNESCO